Corrosion-resistant hot galvanizing foundation bolt and preparation method thereof
By using specific plating agents with specific components and reasonably proportioned constituent materials in hot-dip galvanized anchor bolts, the problem of insufficient corrosion resistance and mechanical strength of hot-dip galvanized anchor bolts in corrosive environments is solved, and significant corrosion resistance and mechanical performance improvements are achieved.
Patent Information
- Application Number
- CN202510079868.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-18
AI Technical Summary
The existing hot-dip galvanized anchor bolts have insufficient corrosion resistance and mechanical strength in environments with strong corrosion, resulting in shortening of service life and unstable mechanical properties.
The anchor bolt body is composed by reasonable proportion of specific ingredients, and the auxiliary plating is carried out before hot-dip galvanizing. Components such as zinc chloride, ammonium chloride, sodium fluoride, monoethyl fumarate and sodium gluconate are added to the auxiliary plating agent to improve the quality and corrosion resistance of the hot-dip galvanized layer.
It significantly improves the corrosion resistance and mechanical strength properties of anchor bolts, extends service life, and ensures its stable performance in various environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anchor bolts, and in particular to a corrosion-resistant hot-dip galvanized anchor bolt and a preparation method thereof. Background Art
[0002] Anchor bolts are components used to fasten mechanical equipment to the ground foundation. They are usually composed of screws, nuts, washers, etc. One end of the bolt is usually buried in the ground foundation, while the other end is connected to the mechanical equipment to be fixed through equipment connectors such as nuts, thereby stabilizing the equipment and preventing it from shifting or shaking.
[0003] Hot-dip galvanized anchor bolts are anchor bolts that have been treated with a special hot-dip galvanizing process. During the treatment process, the anchor bolts will first undergo pre-treatment steps such as pickling, and then be immersed in high-temperature zinc liquid to make the zinc layer firmly adhere to the surface of the bolts to form a protective film. This zinc protective film can help improve the corrosion resistance of the bolts, and is particularly suitable for buildings and facilities that are exposed to the atmosphere and are easily corroded by rain, dew, etc., such as outdoor facilities, engineering buildings in coastal areas, and agricultural facilities.
[0004] However, the protective ability of the hot-dip galvanized layer of the anchor bolts is still limited. In some highly corrosive environments, the hot-dip galvanized layer may not be able to ensure the integrity of the anchor bolts for a long time, and may even have an adverse effect on their mechanical strength properties.
[0005] Therefore, developing a hot-dip galvanized anchor bolt with excellent corrosion resistance and mechanical strength is of great significance for extending the service life of the bolt and ensuring its stable performance in various environments. Summary of the invention
[0006] The invention provides a corrosion-resistant hot-dip galvanized anchor bolt and a preparation method thereof, which solves the problems of poor corrosion resistance and poor mechanical strength of the hot-dip galvanized anchor bolt in the related art.
[0007] The technical solution of the present invention is as follows: The present invention provides a corrosion-resistant hot-dip galvanized anchor bolt, which is obtained by hot-dip galvanizing an anchor bolt body. Before the hot-dip galvanizing, the anchor bolt body needs to undergo a plating assistance treatment. The anchor bolt body is composed of the following components in percentage by weight: C 0.28%~0.35%, Mn 0.41%~0.65%, Mo 0.102%~0.244%, Co 0.14%~0.16%, Mg 0.18%~0.28%, Cu 0.2%~0.26%, W 0.135%~0.26%, Al 0.18%~0.26%, Nb 0.008%~0.056%, Y 0.05%~0.08%, S≤0.016%, P≤0.0035%, and the rest are iron and unavoidable impurities.
[0008] As a further technical solution, the ratio of the weight of the Mg to the sum of the weights of the Mo and the Nb is 1≤Mg / (Mo+Nb)≤1.5.
[0009] When the ratio of the weight of Mg to the sum of the weights of Mo and Nb is 1≤Mg / (Mo+Nb)≤1.5, the mechanical properties of the anchor bolt body can be further improved.
[0010] As a further technical solution, the weight ratio of the Mo to the Nb is 9:1.
[0011] As a further technical solution, during the plating aid treatment, the plating aid includes the following components in parts by weight: 32-42 parts of zinc chloride, 8-10 parts of ammonium chloride, 4-8 parts of sodium fluoride, 0.2-0.6 parts of emulsifier, 1-10 parts of monoethyl fumarate, 3-9 parts of sodium gluconate, and 80 parts of water.
[0012] In the present invention, zinc chloride is a key component of the plating aid, and it cooperates with ammonium chloride, sodium fluoride, an emulsifier, monoethyl fumarate and sodium gluconate to provide a good foundation for the hot-dip galvanizing process of the anchor bolts during the plating aid treatment process, and effectively improves the quality of the hot-dip galvanized layer. Specifically, when monoethyl fumarate and sodium gluconate are added to the plating aid, the monoethyl fumarate and sodium gluconate are used together to improve the stability of the plating aid, and the galvanized layer in the hot-dip galvanizing process can be made more uniform and stable, thereby improving the corrosion resistance of the hot-dip galvanized anchor bolts.
[0013] As a further technical solution, the weight ratio of the sodium gluconate to the monoethyl fumarate is 1-2:1.
[0014] When the weight ratio of sodium gluconate to monoethyl fumarate is 1-2:1, the corrosion resistance of the hot-dip galvanized anchor bolts can be further improved.
[0015] As a further technical solution, the emulsifier includes one or more of fatty alcohol polyoxyethylene ether, sodium dodecylbenzene sulfonate, and alkylphenol polyoxyethylene ether.
[0016] As a further technical solution, during the hot-dip galvanizing, the zinc liquid is composed of the following components in weight percentage: Fe 0.025%~0.035%, Sn 0.15%~0.25%, Mg 0.06%~0.09%, Si 0.2%~0.4%, and the rest is zinc and its inevitable impurities.
[0017] The present invention also provides a method for preparing the corrosion-resistant hot-dip galvanized anchor bolts, comprising the following steps: S1. Dispensing and smelting the components according to the weight percentage of the anchor bolt body to obtain molten steel; S2, casting and cooling the molten steel to obtain a foundation bolt blank; S3, subjecting the anchor bolt blank to thread processing, heat treatment, and cryogenic treatment to obtain an anchor bolt; S4, after pickling and washing the anchor bolt body with water, placing it in a plating agent for plating treatment to obtain a plating anchor bolt; S5, placing the anchor bolts after the plating assistance in zinc liquid for hot-dip galvanizing treatment, and then finishing, passivating and cooling to obtain hot-dip galvanized anchor bolts.
[0018] As a further technical solution, in step S3, during the heat treatment, the temperature is raised to 600~800°C, kept warm for 1~2 hours, and then cooled to room temperature; during the deep cold treatment, the temperature is -60~-80°C and the time is 1~2 hours.
[0019] As a further technical solution, in step S4, the plating assist treatment is performed for 3 to 6 minutes.
[0020] As a further technical solution, in step S5, the temperature of the zinc solution is 450-540°C, the hot dip galvanizing time is 20-30s, and the galvanizing amount is 40-70g / m 2 .
[0021] The working principle and beneficial effects of the present invention are: In the present invention, the anchor bolt body is formed by a reasonable ratio of specific components, which has good mechanical properties and can be applied to the fields of construction, industry, etc. where the stability of structural connection is required to be high. Among them, by reasonably regulating the contents of Mg, Mo and Nb, the strength performance of the anchor bolt body under stress can be significantly enhanced, thereby meeting harsh and complex mechanical conditions. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In the following embodiments and comparative examples, the Mn content in the manganese-iron alloy is 75wt%; the Mo content in the molybdenum-iron alloy is 60wt%; the Co content in the iron-cobalt alloy is 50wt%; the Mg content in the magnesium ingot is 99.95wt%; the Cu content in the copper-iron alloy is 90wt%; the W content in the tungsten-iron alloy is 75wt%; the Al content in the aluminum ingot is 99.8wt%; the Nb content in the niobium-iron alloy is 70wt%; the Y content in the yttrium-iron alloy is 60wt%; the Fe content in the scrap steel is 97wt%; and the model of the fatty alcohol polyoxyethylene ether is AEO-9.
[0024] Example 1 A corrosion-resistant hot-dip galvanized anchor bolt is obtained by hot-dip galvanizing an anchor bolt body. Before hot-dip galvanizing, the anchor bolt body needs to undergo a plating treatment. The anchor bolt body is composed of the following components in weight percentage: C 0.28%, Mn 0.41%, Mo 0.102%, Co 0.14%, Mg 0.18%, Cu 0.2%, W 0.135%, Al 0.18%, Nb 0.008%, Y 0.05%, S 0.003%, P 0.001%, the rest are iron and unavoidable impurities; During the plating aid treatment, the plating aid includes the following components in parts by weight: 32 parts of zinc chloride, 8 parts of ammonium chloride, 4 parts of sodium fluoride, 0.2 parts of fatty alcohol polyoxyethylene ether, 1 part of monoethyl fumarate, 3 parts of sodium gluconate, 80 parts of water; During hot-dip galvanizing, the zinc solution is composed of the following components in weight percentage: Fe 0.025%, Sn 0.15%, Mg 0.06%, Si 0.2%, the rest is zinc and its inevitable impurities; The preparation method of hot-dip galvanized anchor bolts comprises the following steps: S1. Mixing and smelting ferromanganese alloy, ferromolybdenum alloy, iron-cobalt alloy, magnesium ingot, copper-ferroalloy, ferrotungsten alloy, aluminum ingot, ferroniobium alloy, ferroydtrium alloy and scrap steel according to the weight percentage of the anchor bolt body to obtain molten steel; S2, casting and cooling the molten steel to obtain a foundation bolt blank; S3, after thread processing of the anchor bolt blank, heating to 600°C and keeping the temperature for 2 hours, cooling to room temperature, completing the heat treatment, and then performing deep cryogenic treatment at -60°C for 2 hours to obtain the anchor bolt; S4, after pickling and washing the anchor bolt body, placing it in a plating agent for plating treatment, after the plating treatment for 6 minutes, obtaining the plating anchor bolt; S5. Place the anchor bolts after galvanizing in 450℃ zinc solution for hot dip galvanizing. After 30s, the galvanizing amount is 70g / m 2 After finishing, passivation and cooling, hot-dip galvanized anchor bolts are obtained.
[0025] Example 2 A corrosion-resistant hot-dip galvanized anchor bolt is obtained by hot-dip galvanizing an anchor bolt body. Before hot-dip galvanizing, the anchor bolt body needs to undergo a plating treatment. The anchor bolt body is composed of the following components in weight percentage: C 0.32%, Mn 0.5%, Mo 0.189%, Co 0.15%, Mg 0.19%, Cu 0.23%, W 0.2%, Al 0.22%, Nb 0.021%, Y 0.065%, S 0.01%, P 0.002%, the rest are iron and unavoidable impurities; During the plating aid treatment, the plating aid includes the following components in parts by weight: 37 parts of zinc chloride, 9 parts of ammonium chloride, 6 parts of sodium fluoride, 0.4 parts of fatty alcohol polyoxyethylene ether, 8 parts of monoethyl fumarate, 4 parts of sodium gluconate, 80 parts of water; During hot-dip galvanizing, the zinc solution is composed of the following components in weight percentage: Fe 0.03%, Sn 0.2%, Mg 0.08%, Si 0.3%, the rest is zinc and its inevitable impurities; The preparation method of hot-dip galvanized anchor bolts comprises the following steps: S1. Mixing and smelting ferromanganese alloy, ferromolybdenum alloy, iron-cobalt alloy, magnesium ingot, copper-ferroalloy, ferrotungsten alloy, aluminum ingot, ferroniobium alloy, ferroydtrium alloy and scrap steel according to the weight percentage of the anchor bolt body to obtain molten steel; S2, casting and cooling the molten steel to obtain a foundation bolt blank; S3, after thread processing of the anchor bolt blank, heating to 700°C and keeping the temperature for 1.5 hours, cooling to room temperature, completing the heat treatment, and then performing deep cryogenic treatment at -70°C for 1.5 hours to obtain the anchor bolt; S4, after pickling and washing the anchor bolt body, placing it in a plating agent for plating treatment, after the plating treatment for 4.5 minutes, obtaining the plating anchor bolt; S5. Place the anchor bolts after galvanizing in 490℃ zinc solution for hot dip galvanizing. After 25s, the galvanizing amount is 55g / m 2 After finishing, passivation and cooling, hot-dip galvanized anchor bolts are obtained.
[0026] Example 3 A corrosion-resistant hot-dip galvanized anchor bolt is obtained by hot-dip galvanizing an anchor bolt body. Before hot-dip galvanizing, the anchor bolt body needs to undergo a plating treatment. The anchor bolt body is composed of the following components in weight percentage: C 0.35%, Mn 0.65%, Mo 0.244%, Co 0.16%, Mg 0.28%, Cu 0.26%, W 0.26%, Al 0.26%, Nb 0.056%, Y 0.08%, S 0.016%, P 0.0035%, the rest are iron and unavoidable impurities; During the plating aid treatment, the plating aid includes the following components in parts by weight: 42 parts of zinc chloride, 10 parts of ammonium chloride, 8 parts of sodium fluoride, 0.6 parts of fatty alcohol polyoxyethylene ether, 10 parts of monoethyl fumarate, 9 parts of sodium gluconate, 80 parts of water; During hot-dip galvanizing, the zinc solution is composed of the following components in weight percentage: Fe 0.035%, Sn 0.25%, Mg 0.09%, Si 0.4%, the rest is zinc and its inevitable impurities; The preparation method of hot-dip galvanized anchor bolts comprises the following steps: S1. Mixing and smelting ferromanganese alloy, ferromolybdenum alloy, iron-cobalt alloy, magnesium ingot, copper-ferroalloy, ferrotungsten alloy, aluminum ingot, ferroniobium alloy, ferroydtrium alloy and scrap steel according to the weight percentage of the anchor bolt body to obtain molten steel; S2, casting and cooling the molten steel to obtain a foundation bolt blank; S3, after thread processing of the anchor bolt blank, heating to 800°C and keeping the temperature for 1 hour, cooling to room temperature, completing the heat treatment, and performing deep cryogenic treatment at -80°C for 1 hour to obtain the anchor bolt; S4, after pickling and washing the anchor bolt body, placing it in a plating agent for plating treatment, after plating treatment for 3 minutes, obtaining the plating anchor bolt; S5. Place the anchor bolts after galvanizing in 540℃ zinc solution for hot dip galvanizing. After 20s, the galvanizing amount is 40g / m 2 After finishing, passivation and cooling, hot-dip galvanized anchor bolts are obtained.
[0027] Example 4 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the weight percentage of Mg added is 0.28%, the weight percentage of Mo added is 0.108%, and the weight percentage of Nb added is 0.012%.
[0028] Example 5 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the weight percentage of Mg added is 0.2%, the weight percentage of Mo added is 0.15%, and the weight percentage of Nb added is 0.05%.
[0029] Example 6 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the weight percentage of Mg added is 0.24%, the weight percentage of Mo added is 0.12%, and the weight percentage of Nb added is 0.04%.
[0030] Example 7 The difference between this embodiment and embodiment 6 is that in this embodiment, no sodium gluconate is added to the plating aid, and 12 parts of monoethyl fumarate are added.
[0031] Example 8 The difference between this embodiment and embodiment 6 is that in this embodiment, no monoethyl fumarate is added to the plating aid, and 12 parts of sodium gluconate are added.
[0032] Example 9 The only difference between this embodiment and embodiment 6 is that in this embodiment, monoethyl fumarate and sodium gluconate are not added to the plating aid.
[0033] Example 10 The only difference between this embodiment and embodiment 6 is that in this embodiment, 8.5 parts of sodium gluconate and 3.5 parts of monoethyl fumarate are added to the plating assistant.
[0034] Embodiment 11 The only difference between this embodiment and embodiment 6 is that in this embodiment, 6 parts of sodium gluconate and 6 parts of monoethyl fumarate are added to the plating assistant.
[0035] Example 12 The only difference between this embodiment and embodiment 6 is that in this embodiment, 8 parts of sodium gluconate and 4 parts of monoethyl fumarate are added to the plating assistant.
[0036] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, no Nb is added, the weight percentage of Mg added is 0.18%, and the weight percentage of Mo added is 0.11%.
[0037] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, no Mo is added, the weight percentage of Mg added is 0.18%, and the weight percentage of Nb added is 0.11%.
[0038] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, Nb and Mo are not added, and the weight percentage of Mg added is 0.29%.
[0039] Comparative Example 4 The difference between this comparative example and Example 1 is that in this comparative example, no Mg is added, the weight percentage of Mo added is 0.269%, and the weight percentage of Nb added is 0.021%.
[0040] Comparative Example 5 The only difference between this comparative example and Example 1 is that in this comparative example, Nb, Mo and Mg are not added.
[0041] Test Example 1 Mechanical Properties Test Based on the test method in GB / T 228.1-2021 "Tensile test of metal materials Part 1: Room temperature test method", the tensile strength of the anchor bolt bodies prepared in Examples 1 to 6 and Comparative Examples 1 to 5 was tested, wherein the test rate was 0.008s -1 , the test results are shown in Table 1 below: Table 1 Test results of tensile strength of anchor bolt bodies of Examples 1 to 6 and Comparative Examples 1 to 5
[0042] It can be seen from Table 1 that compared with Comparative Examples 1 to 5, the tensile strength of Example 1 is significantly improved, indicating that when Mg, Mo and Nb are introduced into the anchor bolt body, the mechanical properties of the anchor bolt body can be significantly improved by using Mg, Mo and Nb together.
[0043] Compared with Examples 2 and 4, the tensile strength of Examples 5-6 is improved, indicating that when the ratio of the weight of Mg to the sum of the weights of Mo and Nb is 1≤Mg / (Mo+Nb)≤1.5, the mechanical properties of the anchor bolt body can be further improved.
[0044] Test Example 2 Corrosion resistance test The hot-dip galvanized anchor bolts prepared in Examples 6 to 12 were immersed in a hydrochloric acid aqueous solution with a mass fraction of 18% for 60 minutes, and the corrosion reduction test was performed based on the mass before and after immersion. The corrosion reduction (%) = (mass of hot-dip galvanized anchor bolts before corrosion - mass of hot-dip galvanized anchor bolts after corrosion) / mass of hot-dip galvanized anchor bolts before corrosion × 100%. The test results are as follows: Table 2 Corrosion reduction test results of hot-dip galvanized anchor bolts in Examples 6 to 12
[0045] It can be seen from Table 2 that compared with Examples 7 to 9, the corrosion loss of the hot-dip galvanized anchor bolts in Examples 6 and 10 to 12 is significantly reduced, indicating that when monoethyl fumarate and sodium gluconate are present in the plating aid, monoethyl fumarate and sodium gluconate have a synergistic effect and can improve the corrosion resistance of the hot-dip galvanized anchor bolts.
[0046] Compared with Examples 6 and 10, the corrosion loss of the hot-dip galvanized anchor bolts in Examples 11 to 12 is reduced, indicating that when the weight ratio of sodium gluconate to monoethyl fumarate is 1 to 2:1, the corrosion resistance of the hot-dip galvanized anchor bolts can be further improved.
[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A corrosion-resistant hot-dip galvanized anchor bolt, which is obtained by hot-dip galvanizing the anchor bolt body. Before hot-dip galvanizing, it needs to undergo a plating-assisting treatment, characterized in that: The anchor bolt body is composed of the following components in percentage by weight: C 0.28%~0.35%, Mn 0.41%~0.65%, Mo 0.102%~0.244%, Co 0.14%~0.16%, Mg 0.18%~0.28%, Cu 0.2%~0.26%, W 0.135%~0.26%, Al 0.18%~0.26%, Nb 0.008%~0.056%, Y 0.05%~0.08%, S≤0.016%, P≤0.0035%, and the rest are iron and unavoidable impurities.
2. The corrosion-resistant hot-dip galvanized anchor bolt according to claim 1, characterized in that: The ratio of the weight of the Mg to the sum of the weights of the Mo and the Nb is 1≤Mg / (Mo+Nb)≤1.
5.
3. The corrosion-resistant hot-dip galvanized anchor bolt according to claim 1, characterized in that: The weight ratio of the Mo to the Nb is 9:
1.
4. The corrosion-resistant hot-dip galvanized anchor bolt according to claim 1, characterized in that: During the plating aid treatment, the plating aid comprises the following components in parts by weight: 32-42 parts of zinc chloride, 8-10 parts of ammonium chloride, 4-8 parts of sodium fluoride, 0.2-0.6 parts of emulsifier, 1-10 parts of monoethyl fumarate, 3-9 parts of sodium gluconate, and 80 parts of water.
5. The corrosion-resistant hot-dip galvanized anchor bolt according to claim 4, characterized in that: The weight ratio of the sodium gluconate to the monoethyl fumarate is 1-2:
1.
6. The corrosion-resistant hot-dip galvanized anchor bolt according to claim 4, characterized in that: The emulsifier includes one or more of fatty alcohol polyoxyethylene ether, sodium dodecylbenzene sulfonate, and alkylphenol polyoxyethylene ether.
7. The corrosion-resistant hot-dip galvanized anchor bolt according to claim 1, characterized in that: During the hot-dip galvanizing, the zinc solution is composed of the following components in percentage by weight: Fe 0.025%~0.035%, Sn 0.15%~0.25%, Mg 0.06%~0.09%, Si 0.2%~0.4%, and the rest is zinc and its inevitable impurities.
8. A method for preparing a corrosion-resistant hot-dip galvanized anchor bolt according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Dispensing and smelting the components according to the weight percentage of the anchor bolt body to obtain molten steel; S2, casting and cooling the molten steel to obtain an anchor bolt blank; S3, subjecting the anchor bolt blank to thread processing, heat treatment, and cryogenic treatment to obtain an anchor bolt; S4, after pickling and washing the anchor bolt body with water, placing it in a plating agent for plating treatment to obtain a plating anchor bolt; S5, placing the anchor bolts after the plating assistance in zinc liquid for hot-dip galvanizing treatment, and then finishing, passivating and cooling to obtain hot-dip galvanized anchor bolts.
9. The method for preparing a corrosion-resistant hot-dip galvanized anchor bolt according to claim 8, characterized in that: In step S3, during the heat treatment, the temperature is raised to 600-800°C, kept at this temperature for 1-2 hours, and then cooled to room temperature; during the cryogenic treatment, the temperature is -60--80°C and the time is 1-2 hours.
10. The method for preparing a corrosion-resistant hot-dip galvanized anchor bolt according to claim 8, characterized in that: In step S4, the plating assist treatment is performed for 3 to 6 minutes.
Citation Information
Patent Citations
Bolt surface zinc plating layer production method
CN103233193A
Tin-containing zinc-aluminum-magnesium cladded steel sheet with spangles and zinc plating method
CN109234571A
Hot dip galvanizing process of corrosion-resistant steel pipe
CN111304572A
Heavy-duty high-strength foundation bolt and preparation method thereof
CN112226675A
Ammonium-free plating assistant and hot galvanizing process using ammonium-free plating assistant
CN115011900A